Optimization of Cumene Production Through Reactive Distillation with Heat Integration - Galang Adi Saputra; Amadeus Vincent Widjaja; Kudrat Sunandar (Institute for Research and Community Service (LPPM), Universitas Malikussaleh, Indonesia, 2025)
This study aims to optimize the cumene production process through reactive distillation by implementing heat integration to enhance energy efficiency and reduce operational costs. Cumene is produced via the alkylation reaction between benzene and propylene in a reactive distillation column, where reaction and product separation occur simultaneously. The research method involves process simulation using Aspen HYSYS software, comparing processes without and with heat integration. Simulation results indicate that heat integration reduces total energy requirements from 48,023 kW to 37,956 kW, achieving an energy saving of 10,067 kW. Additionally, this energy saving translates into an annual operational cost reduction of 377,309. While the amount of cumene produced remains constant at 7,055 kg/hour, heat integration proves effective in reducing costs and improving overall process efficiency. This study concludes that heat integration in reactive distillation is an economical and efficient solution for cumene production, with broad adoption potential in the chemical industry.